FAO/IBPGR technical guidelines for the safe movement of grapevine germplasm - Frison, Emile A.; Ikin, R.; Food and Agriculture Organization of the United Nations; International Plant Genetic Resources Institute (1991)
These guidelines are divided into 2 parts. The first makes general recommendations on how best to move Vitis germplasm (general recommendations, technical recommendations, and therapy and indexing strategy) and mentions institutions recovering and maintaining healthy grape germplasm. The second part covers the important virus, viroid, virus-like, mollicute, bacterial and fungal diseases of quarantine concern. The information given on any particular pathogen concentrates on those aspects most relevant to quarantine. (Abstract © CAB ABSTRACTS, CAB International)